2018
DOI: 10.15252/embj.201798770
|View full text |Cite
|
Sign up to set email alerts
|

The PEAT protein complexes are required for histone deacetylation and heterochromatin silencing

Abstract: In eukaryotes, heterochromatin regions are typically subjected to transcriptional silencing. DNA methylation has an important role in such silencing and has been studied extensively. However, little is known about how methylated heterochromatin regions are subjected to silencing. We conducted a genetic screen and identified an () mutant that releases heterochromatin silencing in We demonstrated that EPCR1 functions redundantly with its paralog EPCR2 and interacts with PWWP domain-containing proteins (PWWPs), A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(97 citation statements)
references
References 85 publications
(169 reference statements)
9
75
0
10
Order By: Relevance
“…Furthermore, our proteomics experiments revealed that Arabidopsis YAF9A interacted with some NuA4-C subunits, and in vivo Co-IP experiments from this work ( Fig. 7d; Dataset S2) and independent pulldown assays involving HAM proteins (Tan et al, 2018) corroborated the interaction with HAM1, consistent with YAF9A being part of this putative HAT complex in plants. Nevertheless, it cannot be ruled out that YAF9 proteins could be nonessential SWR1-C subunits or form part of additional chromatin-remodeling complexes (Zhang et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, our proteomics experiments revealed that Arabidopsis YAF9A interacted with some NuA4-C subunits, and in vivo Co-IP experiments from this work ( Fig. 7d; Dataset S2) and independent pulldown assays involving HAM proteins (Tan et al, 2018) corroborated the interaction with HAM1, consistent with YAF9A being part of this putative HAT complex in plants. Nevertheless, it cannot be ruled out that YAF9 proteins could be nonessential SWR1-C subunits or form part of additional chromatin-remodeling complexes (Zhang et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…1, 2, 3, 5). This unexpected result should be confronted with a recent study showing that, in addition to the pair of EPL1 orthologues described herein, A. thaliana contains two EPL1-related proteins (EPCR) 30 . Despite marginal sequence similarity to EPL1, EPCRs interact physically with HAM1 and HAM2 30 , possibly explaining why essential functions of HAMs and picNuA4 may be completed without AtEPL1.…”
Section: Discussionmentioning
confidence: 58%
“…In fact, our analysis identified only 5 proteins which show no homology to yeast NuA4 subunits as potential AtEPL1B interactors (Table 1, Supplementary Data 2). Two of these proteins, AOG2 and BRD6, were copurified with A. thaliana NuA4 subunits previously, albeit in much larger pools of additional interactors (Table 1) 24,30,36 . Interestingly, the uncharacterized bromodomain protein BRD6 37 , previously copurified with SWC4 24 and HAM1 30 (Table 1), is orthologous to BRD8, a subunit of the human equivalent of NuA4, the TIP60/p400 complex, according to PANTHER Classification System 38,39 , indicating a possible role as an accessory subunit of the plant NuA4.…”
Section: Atepl1 Interacts With the Subunits Of The Nua4's Regulatory mentioning
confidence: 90%
See 1 more Smart Citation
“…In this issue of EMBO Journal, Tan et al () describe a new Arabidopsis silencing complex, PEAT. This is a significant discovery because forward genetic screens have been mostly saturated and it is nowadays relatively uncommon to discover a new major silencing factor.…”
Section: Composition and Function Of The Peat Complexmentioning
confidence: 99%